Multifaceted Functions and Novel Insight Into the Regulatory Role of RNA N6-Methyladenosine Modification in Musculoskeletal Disorders - Zhang, Wenchao; He, Lile; Liu, Zhongyue; Ren, Xiaolei; Qi, Lin; Wan, Lu; Wang, Wanchun; Tu, Chao; Li, Zhihong (Frontiers in Cell and Developmental Biology, 2020)
RNA modifications have emerged as key regulators of transcript expression in diverse physiological and pathological processes. As one of the most prevalent types of RNA modifications, N6-methyladenosine (m6A) has become the highlight in modulation of various diseases through interfering RNA splicing, translation, nuclear export, and decay. In many cases, the detailed functions of m6A in cellular processes and diseases remain unclear. Notably, recent studies have determined the relationship between m6A modification and musculoskeletal disorders containing osteosarcoma, osteoarthritis, rheumatoid arthritis, and osteoporosis, etc. Herein, this review comprehensively summarizes the recent advances of m6A modification in pathogenesis and progression of musculoskeletal diseases. Specifically, the underlying molecular mechanisms, detection technologies, regulatory functions, clinical implications, and future perspectives of m6A in musculoskeletal disorders are discussed, with the aim to provide a novel insight into their association.